Network effects in two-sided markets: Why a 50/50 user split is not necessarily revenue optimal - Sebastian Voigt; Oliver Hinz (Business Research, 2015)
Our study applies empirical scrutiny to the network effects of a leading European online dating platform. While one might expect equal gender representation on such a platform to yield the best user experience and the highest revenue per user, our analysis shows that the platform requires only 36.2 % of its user base to be female to maximize revenue, primarily because women exert stronger positive cross-side network effects on men than vice versa; this optimum results in 17.2 % higher sales than a 50/50 split. Intermediaries of two-sided markets can use our model to improve user acquisition strategies.
Keywords: 650; Network effects; Two-sided markets; Online dating; Willingness to pay; Revenue optimization